2008
DOI: 10.1016/j.physbeh.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of dietary fat and resistance to obesity

Abstract: The task of maintaining energy balance involves not only making sure that the number of calories ingested equals the number of calories burned but also involves ensuring nutrient balance. This means that over time, the quantity of carbohydrate, fat and protein consumed equals the amount of each oxidized. While the body has the ability to convert protein to carbohydrate and carbohydrate to fat, over long periods of time the body establishes nutrient balance with a high degree of accuracy storing excess nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 49 publications
(21 reference statements)
1
27
0
Order By: Relevance
“…However, efforts to suppress energy intake by the stimulation of fatty acid oxidation have failed to consistently show an effect on food intake (82,83). This may be because changes in whole body fat oxidation provide a weak regulatory signal for food intake, with the amount of fat ingested or oxidised on a daily basis very small relative to the total amount of energy stored as adipose tissue (84). Indeed, while it has been suggested that that nutrient metabolism may exert negative feedback on food intake e.g.…”
Section: Body Composition Energy Expenditure and Food Intakementioning
confidence: 99%
“…However, efforts to suppress energy intake by the stimulation of fatty acid oxidation have failed to consistently show an effect on food intake (82,83). This may be because changes in whole body fat oxidation provide a weak regulatory signal for food intake, with the amount of fat ingested or oxidised on a daily basis very small relative to the total amount of energy stored as adipose tissue (84). Indeed, while it has been suggested that that nutrient metabolism may exert negative feedback on food intake e.g.…”
Section: Body Composition Energy Expenditure and Food Intakementioning
confidence: 99%
“…Therefore, only minimal mealrelated fluctuations of hepatic FAO can be expected. In fact, labeling studies demonstrated that ingested fat reaches the liver in substantial amounts not before 2-3 h after the onset of ingestion, i.e., long after meal termination (13). With ad libitum access to food, fatty acids derived from ingested TAG may in fact become available to hepatocytes as an energy source at just about the time when a new meal begins, at least in the rat.…”
Section: Central Vs Peripheral Fatty Acid Sensing Via Oxidationmentioning
confidence: 99%
“…Given the replacement of other nutrients by fats as fuels during the postprandial period, meals may actually be initiated during a gradual increase rather than a decrease in whole body FAO, indicating that the latter does not provide a physiological hunger signal. On the other hand, meal-related changes in the oxidation of dietary triacylglycerol (TAG)-derived fatty acids may occur at critical sensor sites in particular tissues, and ample evidence indicates that differences in FAO or, more specifically, differences in the organism's capacity to increase the oxidation of dietary TAG-derived fatty acids in response to increases in dietary fat intake are one of the factors determining the susceptibility to dietary fat-induced overeating and weight gain (13,65,76,149). A critical question, thus, is where in the body oxidation of dietary TAG-derived fatty acids is monitored to influence energy intake and expenditure.…”
mentioning
confidence: 99%
“…A recent review [23] concluded that the partitioning of dietary fat between tissues might play an important role in the resistance or susceptibility to obesity. The relative metabolism of dietary fat, favoring oxidation over storage, may be associated with more robust signaling of positive energy balance and resistance to dietary-induced obesity.…”
Section: Differences In Substrate Utilization Between Individuals Fedmentioning
confidence: 99%